2019
DOI: 10.15171/jhp.2019.04
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin and mangiferin-containing leaf extract from Mangifera foetida L for therapeutic attenuation of experimentally induced iron overload in a rat model

Abstract: Mangiferin and mangiferin-containing extracts from Mangifera foedita leaves are potent candidates as antioxidant iron chelators in the management of iron-overloaded thalassemia patients and may help to lower the costs of their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[ 60 ] It is relevant to cite herein that ethanolic extract of M. indica leaves of China reported to be contained more than 60% mangiferin, a types of phenolic compounds. [ 61 ] Also, it reported that extracts of mango leaves and mangiferin compound showed good iron‐chelating effects, [ 62 ] and hence the iron‐complexing ability of the methanol extract of M. indica leaves of Nepal origin is expected to be potent for the formation of protective passive film on the surface of steel rods embedded in concrete.…”
Section: Resultsmentioning
confidence: 99%
“…[ 60 ] It is relevant to cite herein that ethanolic extract of M. indica leaves of China reported to be contained more than 60% mangiferin, a types of phenolic compounds. [ 61 ] Also, it reported that extracts of mango leaves and mangiferin compound showed good iron‐chelating effects, [ 62 ] and hence the iron‐complexing ability of the methanol extract of M. indica leaves of Nepal origin is expected to be potent for the formation of protective passive film on the surface of steel rods embedded in concrete.…”
Section: Resultsmentioning
confidence: 99%
“…Medicinal plant usually have mul-tifunction properties [22][23][24][25][26][27][28]. The shortcomings of the current treatments can be completed by medicinal plants which not only are able to target multiple organs of the body but also can reduce their toxic effects [29][30][31][32][33]. Most laxative medicinal plants have substances such as anthraquinones which stimulate the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…The iron overload and treatment groups received an intraperitoneal injection of 0.75 mL of iron sucrose containing 15 mg of elemental iron every 3-4 days for 8 weeks, for a total dose of 225 mg/rat. After being injected with iron sucrose for 3 weeks to induce iron overload condition (Estuningtyas, Wahyuni, et al, 2019), the treatment group received either deferiprone 462.5 mg/kg BW (D), mangiferin 50 mg/kg BW (M), mahkota dewa fruit extract 100 mg/kg (PM1) and 200 mg/kg BW (PM2) orally once a day for 28 days. At the end of the study, all rats were anesthetized (ketamine-xylazine) and euthanized exsanguination via cardiac puncture.…”
Section: Animal Treatmentsmentioning
confidence: 99%